Modification of the existing maximum residue levels for sulfoxaflor in various crops. (26th April 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Cabrera, Luis Carrasco; Castellan, Irene; Ferreira, Lucien; Giner, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; Magrans, Jose Oriol; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Dow AgroSciences Ltd submitted a request to the competent national authority in Greece to modify the existing maximum residue levels (MRLs) for the active substance sulfoxaflor in lettuce and salad plants (except lettuce), beans with pods and peas without pods. The data submitted in support of the request were found to be sufficient to derive MRL proposals for all crops under consideration. Adequate analytical methods for enforcement are available to control the residues of sulfoxaflor in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of sulfoxaflor according to the reported agricultural practices is unlikely to present a risk to consumer health.